KESANTUNAN TINDAK TUTUR DALAM PANDUAN MITIGASI BENCANA G EMPA BUMI JEPANG - Asteria Permata Martawijaya; Maria Gustini; fajar fathurahman (Universitas Diponegoro, 2024)
This study aims to describe the politeness of representative speech acts and directive speech acts used in NPO-Volcano’s disaster mitigation guideline materials. The method used on this research is descriptive method with data classification based on Searle (1979)’s illocutionary speech acts category and Brown & Levinson (1987)’s politeness scale of speech acts. On the NPO-Volcano disaster mitigation guide material found 41 data of the representative speech acts, which were used for (1) the stating function, (2) the speculating function, (3) the informing function, (4) the mentioning function, (5) the explaining function, and (6) the suggesting function. For the directive speech acts, 30 data were found, which were divided into three types of speech functions, the command function that used in form of verb e, te kudasai, mashou, the inviting function and the prohibiting function. Furthermore, when analyzed using Brown and Levinson's (1987) Politeness Theory, the representative and directive speech acts in the NPO-Volcano disaster mitigation material guide is using “bold on record” and “negative politeness” type of Brown and Levinson's (1987) politeness theory. The forms of negative politeness used are: the use of indirect expressions, respectful language, impersonalization and nominalization. <a href=